2014
DOI: 10.1038/pr.2014.118
|View full text |Cite
|
Sign up to set email alerts
|

MBL2 gene polymorphisms increase the risk of adverse neurological outcome in preterm infants: a preliminary prospective study

Abstract: Background: As described in animal models, the lectincomplement pathway is central to the propagation of ischemia-reperfusion injuries in many tissues, including the brain. Similarly, it might affect the genesis of brain damage in preterm infants. MBL2 gene single-nucleotide polymorphisms (SNPs), regulating mannose-binding lectin (MBL) serum levels, could predict the risk of adverse neurological outcome in these infants. Methods: To evaluate the association between SNPs of the MBL2 gene and long-term neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The authors suggested that this may reflect the negative effect of an increased infection rate in genetically deficient subjects. We reached the same conclusion in a previous study concerning the effect of MBL2 genotypes on neurological outcomes in preterm infants (36). Surprisingly, in a recent letter, Kim et al reported that the mutation in exon 1, codon 54 of MBL2 is protective in babies who underwent single reconstructive ventricle surgery, based on the results obtained for the Psychomotor Developmental Index and Mental Developmental Index at 14 months, which conflicts with their previous findings (37).…”
Section: Discussionsupporting
confidence: 80%
“…The authors suggested that this may reflect the negative effect of an increased infection rate in genetically deficient subjects. We reached the same conclusion in a previous study concerning the effect of MBL2 genotypes on neurological outcomes in preterm infants (36). Surprisingly, in a recent letter, Kim et al reported that the mutation in exon 1, codon 54 of MBL2 is protective in babies who underwent single reconstructive ventricle surgery, based on the results obtained for the Psychomotor Developmental Index and Mental Developmental Index at 14 months, which conflicts with their previous findings (37).…”
Section: Discussionsupporting
confidence: 80%
“…The findings are consistent with other studies in juvenile and pediatric subjects that demonstrate that MBL deficiency is associated with worse neurologic outcomes, [3][4][5] although an opposite effect has been reported in mature subjects. 6,7 This paradox of apparently contradictory implications of MBL deficiency, with outcomes that are better or worse depending on age, is mirrored in the present study wherein the MBL-deficient cohort had worse neurologic outcomes but shorter (ie, better) length of hospital stay.…”
supporting
confidence: 92%
“…So, the effect of MBL2 SNPs on neurological development could be indirect in these infants, perhaps mediated by the infection, and the brain damage induced by MBL deficiency may be partially independent of complement cascade, less active in such preterm infants than in more mature babies and in adults. Other MBL mediated mechanisms, related to the marked brain immaturity of neonates, may have a role in the genesis of the neurological damage [ 8 ].…”
Section: Mbl: Clinical Significancementioning
confidence: 99%
“…While low MBL serum levels have been associated to an increased risk of nosocomial sepsis [ 6 , 7 ] and of neurological risks [ 8 ] in neonates, recent studies performed in rodents support the role of MBL in the exacerbation of tissue damage (myocardial, gastrointestinal, cerebral, and renal tissues) in the course of ischemia-reperfusion injuries, by the activation of the lectin pathway of the complement. According to these data, we found that MBL-2 genotypes associated with high MBL serum levels represent a risk factor for necrotizing enterocolitis (NEC) in preterm neonates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%